2007
DOI: 10.2174/138161207780618939
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Methyl Erythritol Phosphate (MEP) Pathway for Novel Antimalarial, Antibacterial and Herbicidal Drug Discovery: Inhibition of 1-Deoxy-D-Xylulose-5-Phosphate Reductoisomerase (DXR) Enzyme

Abstract: The 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway for isoprenoid biosynthesis has come under increased scrutiny as a target for novel antimalarial, antibacterial and herbicidal agents. 1-Deoxy-D-xylulose 5-phosphate reductoisomerase (DXR) is a key enzyme of the pathway that catalyzes the rearrangement and nicotinamide adenine dinucleotide phosphate (NADPH)-dependent reduction of 1-deoxy-D-xylulose 5-phosphate (DXP) to MEP. The unique properties of DXR make it a remarkable and rational target for drug desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 115 publications
0
111
1
Order By: Relevance
“…The generated pharmacophore model was validated by a test database of 50 known inhibitors (Altincicek et al 2000;Singh et al 2007;Deng et al 2011;Jansson et al 2013) of PfDXR enzyme.…”
Section: Pharmacophore Model Generation and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The generated pharmacophore model was validated by a test database of 50 known inhibitors (Altincicek et al 2000;Singh et al 2007;Deng et al 2011;Jansson et al 2013) of PfDXR enzyme.…”
Section: Pharmacophore Model Generation and Validationmentioning
confidence: 99%
“…From previous literature, a test database of fifty known inhibitors (Altincicek et al 2000;Singh et al 2007;Deng et al 2011;Jansson et al 2013), having 37 active and 13 inactive compounds, was used for the validation of the pharmacophore model. The three dimensional structures of the test database compound were modelled using MOE.…”
Section: Generation and Validation Of Pharmacophore Modelmentioning
confidence: 99%
“…However, the antibiotic was only partially efficient since a recrudescence was observed in 50 % of cases, certainly due to the short half-life of fosmidomycin (Lell et al, 2003). Research of fosmidomycin derivatives with higher efficiency, longer half-life and better absorption are in progress as well as the study of the other enzymes of the pathway (Singh et al, 2007). Interestingly, fosmidomycin has synergic effect with the antibiotic clindamycin and randomized controlled trials in Gabon showed that the association of both molecules is as efficient as the sulfadoxine-pyrimethamine combination in malaria treatment (Oyakhirome et al, 2007).…”
Section: Isoprenoid Pathwaymentioning
confidence: 99%
“…This pathway is different to that of the mevalonate pathway in the human host, making this enzyme an attractive anti-malarial drug target [1]. Recently PfDXR was genetically validated using a single cross-over strategy, and the enzyme was found to be essential for intraerythrocytic development of the parasite, further validating this enzyme as a chemotherapeutic target [2].…”
Section: Introductionmentioning
confidence: 99%